Anterior cruciate ligament deficiency versus intactness for outcomes in patients after unicompartmental knee arthroplasty: a systematic review and meta-analysis - Guo, Weiming; Wan, Teng; Tan, Haifeng; Fan, Gang; Gao, Xiaoyu; Liu, Pan; Jiang, Changqing (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Objective The unicondylar knee arthroplasty (UKA) procedure is primarily indicated for osteoarthritis of the knee. Anterior cruciate ligament (ACL) defects have long been considered a contraindication to UKA. However, recent clinical studies have found that ACL defects do not affect postoperative outcomes in UKA. To elucidate whether ACL defects affect postoperative outcomes in UKA, we performed a systematic review and Meta-analysis of observational cohort studies comparing the effects of ACL defects and intactness on surgical outcomes in UKA. Methods The three databases PubMed, Embase and Cochrane were systematically searched at 12/09/2021. The study used a random effects model to combine effect estimates of 95% confidence intervals (CIs). To explore the sources of heterogeneity and to test the stability of the results, a sensitivity analysis was performed. Results Overall, the postoperative revision (OR, 1.174; 95CI, 0.758-1.817), Tegner activity score (OR, -0.084; 95CI, -0.320-0.151), and Oxford Knee Score (OKS) (OR, -0.065; 95CI, -0.193- 0.063) were not statistically different. Conclusion There was no difference in postoperative revision rates and functional outcomes such as Tegner activity score and OKS between the ACL-deficient group compared with the ACL-intact group. For the present results, it is not advisable to consider ACL deficiency as a contraindication of UKA.